Pengaruh Agama bagi Penderita Diabetes Mellitus dalam Menjalani Kehidupan - Adi Antoni; Haslinah Ahmad; Anto J. Hadi; Abdullah AA (Jurnal Riset Hesti Medan, 2022)
Diabetes mellitus (DM) is a non-communicable disease that is targeted for action by world leaders. DM is part of a hyperglycaemia syndrome that can cause various complaints. Spiritual and religious beliefs (Religion) can help in providing support, confidence, and hope in overcoming chronic diseases. The purpose of this study was to determine the effect of religion on Diabetes Mellitus Patients related to the patient's relationship with God. The type of research is qualitative with Phenomenological study research design.Participants numbered 6 people, the sampling technique of this study was purposive sampling.The results obtained in the form of themes discussed linking theory and previous research.In this study all respondents have different perspectives and backgrounds so that they have different responses. The themes determined based on the results of the interview are 3 themes that describe the Religious Experience of Diabetes Mellitus Patients. These themes are (1) Sources of strength in dealing with DM disease, (2) Obstacles in carrying out worship, (3) Hope in undergoing DM. The conclusion of this study is that Diabetes mellitus patients have a close relationship with religiosity as a source of strength and hope for the desire for healing from diabetes mellitus they suffer from to continue living.